Obscurin Targets Ankyrin-B and Protein Phosphatase 2A to the Cardiac M-line - Cunha, Shane R.; Mohler, Peter J. (The Journal of biological chemistry, 2008)
Ankyrin-B targets ion channels and transporters in excitable cells. Dysfunction in ankyrin-B-based pathways results in defects in cardiac physiology. Despite a wealth of knowledge regarding the role of ankyrin-B for cardiac function, little is known regarding the mechanisms underlying ankyrin-B regulation. Moreover, the pathways underlying ankyrin-B targeting in heart are unclear. We report that alternative splicing regulates ankyrin-B localization and function in cardiomyocytes. Specifically, we identify a novel exon (exon 43′) in the ankyrin-B regulatory domain that mediates interaction with the Rho-GEF obscurin. Ankyrin-B transcripts harboring exon 43′ represent the primary cardiac isoform in human and mouse. We demonstrate that ankyrin-B and obscurin are co-localized at the M-line of myocytes and co-immunoprecipitate from heart. We define the structural requirements for ankyrin-B/obscurin interaction to two motifs in the ankyrin-B regulatory domain and demonstrate that both are critical for obscurin/ankyrin-B interaction. In addition, we demonstrate that interaction with obscurin is required for ankyrin-B M-line targeting. Specifically, both obscurin-binding motifs are required for the M-line targeting of a GFP-ankyrin-B regulatory domain. Moreover, this construct acts as a dominant-negative by competing with endogenous ankyrin-B for obscurin-binding at the M-line, thus providing a powerful new tool to evaluate the function of obscurin/ankyrin-B interactions. With this new tool, we demonstrate that the obscurin/ankyrin-B interaction is critical for recruitment of PP2A to the cardiac M-line. Together, these data provide the first evidence for the molecular basis of ankyrin-B and PP2A targeting and function at the cardiac M-line. Finally, we report that ankyrin-B R1788W is localized adjacent to the ankyrin-B obscurin-binding motif and increases binding activity for obscurin. In summary, our new findings demonstrate that ANK2 is subject to alternative splicing that gives rise to unique polypeptides with diverse roles in cardiac function.